The dark side of nighttime all-terrain vehicle use - Charles A. Jennissen; Nicholas R. Stange; AnnaMarie Fjeld; Gerene M. Denning (BMC, 2021)
Abstract Background Driving at night is considered a risk factor for all-terrain vehicle (ATV) crashes and injuries but few studies have addressed this issue. Our objective was to compare daytime and nighttime ATV crashes to better understand the potential risk factors associated with riding at night. Methods A retrospective study was conducted on Iowa ATV-related crashes and injuries from January 1, 2002 through December 31, 2019 using four statewide datasets: the Iowa Department of Transportation (2002-2019), the Iowa Department of Natural Resources (2002-2019), the Iowa State Trauma Registry (2002-2018) and Iowa newspaper clippings (2009-2019). A standardized coding system was developed, and matching records were identified using Link Plus®. Descriptive (frequencies) and bivariate (chi-square, Fisher's exact test) analyses were performed using VassarStats (Statistical Computation Website). Results Among crash victims where light conditions were documented (2125/3752, 57%), about one-quarter (485/2125, 23%) were injured at night. Nighttime crash victims were less likely youth (14% vs. 30%, p < 0.0001), less likely to be wearing helmets (11% vs. 18%, p = 0.003), and less frequently involved in motor vehicle crashes (7% vs. 14%, p < 0.0001) as compared to daytime victims. Nighttime victims were also more likely to be passengers (22% vs. 15%, p = 0.002), to test positive for alcohol (44% vs. 13% in adults, p < 0.0001), and to be injured on a roadway (53% vs. 45%, p = 0.007) and on weekends (76% vs. 63%, p < 0.0001). Numerous differences between daytime and nighttime characteristics were observed for males, females, and adults, whereas most characteristics were similar for youth. The severity of injuries and proportion of fatalities were similar among daytime and nighttime crash victims. Conclusions Nighttime crash victims, particularly adults, were characterized by more frequent risky behaviors like carrying passengers, roadway riding, alcohol use, and lack of helmets. Whereas the frequency of risky behaviors among youth was similar for daytime and nighttime crashes, these behaviors put children at potential risk for injury. Multi-factorial, targeted injury prevention strategies are needed, including improved vehicle design, education about the dangers of nighttime operation, and passage and enforcement of ATV safety laws. Particularly relevant to our study are laws that prohibit nighttime riding.